2014
DOI: 10.1111/obr.12204
|View full text |Cite
|
Sign up to set email alerts
|

Outside‐of‐school time obesity prevention and treatment interventions in African American youth

Abstract: SummaryOutside-of-school time (OST; i.e. before/after-school hours, summer time), theory-based interventions are potential strategies for addressing increased obesity among African American youth. This review assessed interventions across multiple settings that took place during OST among African American youth aged 5-18 years old. Seven databases were searched for studies published prior to October 2013; 28 prevention and treatment interventions that assessed weight or related behaviours as a primary or secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 62 publications
(358 reference statements)
1
23
0
Order By: Relevance
“…. However, the evidence to date does not provide clear guidance as to the nature or degree of cultural or contextual adaptations that can increase intervention effectiveness . Outcomes of studies involving cultural adaptations are not necessarily better than those observed in non‐adapted studies, although comparisons of these types of programmes are confounded by other differences in the interventions.…”
Section: Key Themes and Research Directionsmentioning
confidence: 99%
“…. However, the evidence to date does not provide clear guidance as to the nature or degree of cultural or contextual adaptations that can increase intervention effectiveness . Outcomes of studies involving cultural adaptations are not necessarily better than those observed in non‐adapted studies, although comparisons of these types of programmes are confounded by other differences in the interventions.…”
Section: Key Themes and Research Directionsmentioning
confidence: 99%
“…The paucity and heterogeneity of evidence for assessing effects of obesity‐related interventions with children and adults in black and other high‐risk populations has been all too common in reviews of both individual behaviour change studies and environmental and policy change evaluations . This is also a consistent conclusion of the other reviews in this special focus issue on obesity interventions in black Americans, which include studies published since May 2009 .…”
Section: Discussionmentioning
confidence: 77%
“…Both school-based [45] and out-of-school [46] programs can directly engage teens in health behavior change. Health care providers can actively support efforts to improve and scale such community-based initiatives.…”
Section: Treatmentmentioning
confidence: 99%